Assessment of the influence of different doses of liquid organic formulations on growth, flowering and yield attributes of strawberry (Fragaria × ananassa) cv. Camarosa under black polyethylene mulch - CHAMOLI, GAURAV; SINGH, KH CHANDRAKUMAR; MANJU; MEWAR, DEEPAK; SEMWAL, SHIKHAR; BAHUGUNA, PANKAJ; WATT, HAOBIJAM JAMES; GOSWAMI, GARGI; BHOSALE, TEJAS ASHOK; SERAM, DEVINA (The Indian Journal of Agricultural Sciences, 2026)
The experiment was conducted for two consecutive seasons from 2022–2023 at College of Horticulture, Veer Chandra Singh Garhwali Uttarakhand University of Horticulture and Forestry, Bharsar, Uttarakhand in a naturally ventilated polyhouse by using five different liquid organic formulations (Jeevamrut, Amritpani, Seaweed extract, Vermiwash, Humic acid ) with three different doses, taking strawberry (Fragaria × ananassa Duch.) cv. Camarosa as the test crop. The experiment was laid out on a randomised complete block design (RCBD) in triplicate. Certain plant growth parameters, yield and economic parameters were taken into consideration for drawing conclusions in the study. In the majority of the traits, humic acid (HA) @3% outperformed and proved significantly higher yield over the rest of the treatments, 256.67% higher yield over the control. Even though the profitability of a production system largely depends on yield, there is a necessity for considering the input cost incurred in the production as well. HA @1%, even though it produced a lesser yield as compared to HA @3%, proved the most profitable input (C:B, 1:4.38) due to the lesser input cost, though there shall be a 9% compromise in yield as compared to HA @3%. Yet, HA @1% scored 198.4% higher yield over the control. Thereby, farmers can derive a promising return of 4.38 fold profit from their investments.